Rheumatoid arthritis and osteoimmunology: The adverse impact of a deregulated immune system on bone metabolism - Andreev, Darja; Kachler, Katerina; Bozec, Aline; Schett, Georg (Bone, 2022)
The term osteoimmunology describes an interdisciplinary research field that links the investigation of osteology (bone cells) with immunology. The crosstalk between innate and adaptive immune cells and cells involved in bone remodeling, mainly bone-resorbing osteoclasts and bone-forming osteoblasts, becomes particularly obvious in the inflammatory autoimmune disease rheumatoid arthritis (RA). Besides striking inflammation of the joints, RA causes bone loss, leading to joint damage and disabilities as well as generalized osteoporosis. Mechanistically, RA-associated immune cells (macrophages, T cells, B cells etc.) produce high levels of pro-inflammatory cytokines, receptor activator of nuclear factor κB ligand (RANKL) and autoantibodies that promote bone degradation and at the same time counteract new bone formation. Today, antirheumatic therapy effectively ceases joint inflammation and arrests bone erosion. However, the repair of established bone lesions still presents a challenging task and requires improved treatment options. In this review, we outline the knowledge gained over the past years about the immunopathogenesis of RA and the impact of a dysregulated immune system on bone metabolism.
CRIS-Team Scopus Importer:2022-07-01
Keywords: Bone erosion; Osteoblasts; Osteoclasts; Osteoimmunology; Rheumatoid arthritis